2018
DOI: 10.3389/fmicb.2018.01215
|View full text |Cite
|
Sign up to set email alerts
|

A Preclinical Model for the ATLL Lymphoma Subtype With Insights Into the Role of Microenvironment in HTLV-1-Mediated Lymphomagenesis

Abstract: Adult T cell Leukemia/Lymphoma (ATLL) is a mature T cell malignancy associated with Human T cell Leukemia Virus type 1 (HTLV-1) infection. Among its four main clinical subtypes, the prognosis of acute and lymphoma variants remains poor. The long latency (3–6 decades) and low incidence (3–5%) of ATLL imply the involvement of viral and host factors in full-blown malignancy. Despite multiple preclinical and clinical studies, the contribution of the stromal microenvironment in ATLL development is not yet completel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 82 publications
0
18
0
Order By: Relevance
“…Thus, efforts have been made to prevent HTLV-1-associated carcinogenesis, and recently, a therapy targeting C-C motif chemokine receptor 4, which has been identified as an adult T-cell leukemia-specific marker associated with HTLV-1, has been clinically tested in Japan with promising results (15). Previous studies explored the mechanisms underlying HTLV-1-mediated tumorigenesis, including the promotion of cell proliferation and modulation of multiple host factors in liver cancer and lymphoma (1618). HTLV-1 differs from other acute transforming retroviruses, and may not rapidly initiate carcinogenesis or alter the expression pattern of cellular proto-oncogenes (16).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, efforts have been made to prevent HTLV-1-associated carcinogenesis, and recently, a therapy targeting C-C motif chemokine receptor 4, which has been identified as an adult T-cell leukemia-specific marker associated with HTLV-1, has been clinically tested in Japan with promising results (15). Previous studies explored the mechanisms underlying HTLV-1-mediated tumorigenesis, including the promotion of cell proliferation and modulation of multiple host factors in liver cancer and lymphoma (1618). HTLV-1 differs from other acute transforming retroviruses, and may not rapidly initiate carcinogenesis or alter the expression pattern of cellular proto-oncogenes (16).…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of the tumor microenvironment in ATL development is not yet completely unraveled. However, using a transgenic and humanized mouse model, Vicario et al showed that fibroblasts might enhance tumorigenesis of HTLV-1-infected and immortalized T cells, thus shedding light on the microenvironment contribution in ATL pathogenesis (Vicario et al, 2018). Although it is not denied that the direct or indirect ECM remodeling by viruses is involved in tissue infiltration and in the anti-tumor host's immune response, the role of viral biofilm, which is constituted of ECM components involved in cancer pathogenesis, has never been investigated.…”
Section: Biofilm and Cancerogenesismentioning
confidence: 99%
“…In vitro interaction with epithelial and fibroblastic cell-lines was shown to induce apoptosis resistance in primary ATLL cells and ATLL cell lines(18), as well as HTLV1 latency(19). In ATLL models, fibroblasts acquire an activated pro-inflammatory phenotype enhancing tumorigenesis(20). Interestingly, MF and SS cells have the potential to inhibit normal T-cell proliferation and suppress dendritic cells maturation by secreting Th2-type cytokines (21).…”
Section: Immune System In T Cell Neoplasms – Rationale For Immunotherapymentioning
confidence: 99%